AN INDONESIAN POLITICIAN’S LEADERSHIP THROUGH SPEECH DURING COVID-19 PANDEMIC - Merrita, Diah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
During the Covid-19 pandemic, leadership played a crucial role in guiding the direction of a country. This research aims at analyzing speech delivered by the Jakarta Governor, Anies Baswedan, during the Covid-19 pandemic taken from online news media. To explore the identity, relational, and ideational dimensions of the speech, the research employs discourse analysis based on the first three-level framework proposed by Fairclough. The three-skill approach is also utilized to discover leadership values embedded in the Governor’s utterances during the pandemic, focusing on his actions and leadership qualities. The findings of this study reveal that he constructs himself as a leader who has taken actions to tackle the plague, a leader who is strict sentencing anyone who disobeys the regulations, a leader who concerns about his people’s safety, and a leader who works collaboratively rather than ndividually. Other findings also explain that his utterances align with the three-skill approach such as the ability in defining problems, communicating goals, planning, employing social judgment skill, and having knowledge.